A qualitative study to explore fathers' attitudes towards breastfeeding in South West England. (20th March 2019) - Merritt, Rowena; Vogel, Michelle; Ladbury, Patrick; Johnson, Sally
Abstract: Aim: To explore the beliefs, attitudes, and behaviours of fathers towards breastfeeding and how they impact either positively or negatively on their partners' decisions to initiate or continue breastfeeding. Background: Despite policy initiatives at a national and international level and the increased number of baby-friendly hospitals within the UK, breastfeeding rates are slow to rise. Support from both parents has been proven to increase uptake and continuation rates, but there is little research into the emotional experience of fathers when it comes to breastfeeding. Methods: We conducted qualitative interviews with 18 fathers in Wiltshire, England. Principles of grounded theory were used throughout this study to guide the sampling, data collection, and data analysis. Findings: Fathers knew the health benefits of breastfeeding and wanted their child to breastfeed but were unsure of their place in the feeding process because they felt it was not their body. While they were aware of the benefits of breast milk for infants, fathers felt less informed of the practicalities of breastfeeding and the potential challenges they and their partner might have to overcome to breastfeed successfully for the recommended six-month period. Based on these findings, three segments were identified: the problem bonders, the dual bonders, and the pragmatists. All segments were concerned with the well-being of their partner and child and wanted their child to be breastfed. Health professionals can use the results of this study to create prenatal educational resources that take more of a preventive and problem-solving approach as opposed to promoting breastfeeding in efforts to comply with National Health Service guidelines, without offering solutions to common breastfeeding problems.